(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The authors are addressing in the paper the (un)efficiency of the confiscation in Croatia. In order to fully implement confiscation of proceeds of crime, as the measure that guards property rights of the primary owner, is guardian of the principle of justice, and serves the protection of public interest, the authors are proposing three concrete amendments to existing regulation. In addition, the authors explained what protection of property encompasses, having in mind the sui generis character of this measure.